Opioid and Benzodiazepine Withdrawal Syndromes in Trauma ICU Patients: A Prospective Exploratory Study. (April 2020) - Arroyo-Novoa, Carmen Mabel; Figueroa-Ramos, Milagros I.; Balas, Michele; Rodríguez, Pablo; Puntillo, Kathleen A.
Abstract : Objectives: Trauma ICU patients may require high and/or prolonged doses of opioids and/or benzodiazepines as part of their treatment. These medications may contribute to drug physical dependence, a response manifested by withdrawal syndrome. We aimed to identify risk factors, symptoms, and clinical variables associated with probable withdrawal syndrome. Design: Prospective exploratory observational study. Setting: Trauma ICU in large medical center in Puerto Rico. Participants: Fifty patients who received opioids and/or benzodiazepines for greater than or equal to 5 days. Measurements and Main Results: Using an opioid/benzodiazepine withdrawal syndrome checklist developed from research in adult ICU patients, the Diagnostic and Statistical Manual of Mental Disorders-5, and the International Classification of Diseases, 10th Edition, we evaluated patients at baseline and for 72 hours after drug weaning was initiated. Patients received opioid/benzodiazepine (88%), opioid (10%), or benzodiazepine (2%). Probable withdrawal syndrome occurred in 44%, questionable withdrawal syndrome in 20%, and no withdrawal syndrome in 18 (36%). Signs that were more frequent in the probable withdrawal syndrome group were agitation, diarrhea, fever, tachypnea, lacrimation, and hyperactive delirium. Patients who developed probable withdrawal syndrome spent almost double the amount of time receiving mechanical ventilation, and length of stay was higher in both ICU and hospital when compared with patients in the other two groups. Age, cumulative opioid dose amounts, and previous drug (opioid/benzodiazepine, cannabis, cocaine, or heroin) use were associated with odds of developing withdrawal syndrome. With the addition of Richmond Agitation-Sedation Scale and delirium to the multilevel analysis, older age no longer had its protective effect, whereas increase in Richmond Agitation-Sedation Scale scores, delirium presence, and increased duration of mechanical ventilation were associated with higher odds of withdrawal syndrome. Conclusions: We identified probable withdrawal syndrome in a sample of trauma ICU patients through observation of several associated symptoms. Significant factors associated with withdrawal syndrome found in this study should be considered when caring for patients being weaned from opioids and/or benzodiazepines. Further validation of the opioid/benzodiazepine withdrawal syndrome checklist is recommended. Abstract : Supplemental Digital Content is available in the text.